Disempowering women-a mixed methods study exploring informational support about pain persisting after childbirth and its consequences - Beata Molin; Sofia Zwedberg; Anna-Karin Berger; Anna Sand; Susanne Georgsson (BMC, 2022)
Abstract Background Access to information is essential to achieving individual empowerment; meaning the ability to exercise control, manage one's own condition and make informed decisions. However, studies have shown that information provided to women regarding physiological changes during the postpartum period and postpartum health was inadequate, incorrect, or inconsistent. Methods The aim of this study was to explore informational support about pain persisting after childbirth and its consequences. A sequential explanatory mixed methods design was used. In the first, quantitative phase, 1,171 women, who gave birth eight months earlier, completed a self-administered questionnaire. In the second, qualitative phase, 20 women who experienced chronic pain were interviewed. Descriptive statistics and qualitative content analysis were used to analyse the data. Results The majority of the women did not receive information about pain persisting after childbirth, or the information was insufficient or incorrect. They did not know when and where to seek help and did not consult health care professionals. In addition, the lack of information had a negative impact on women's psychological well-being. All women expressed the need to be informed by health care professionals, irrespective of the individual risk of developing chronic pain. Conclusions Health services should ensure availability of information to give the women opportunity to achieve empowerment to make good health decisions, increase control over their health and well-being as well as to enhance their self-efficacy. We propose that a booklet or leaflet with relevant information about the risk of developing chronic pain, symptoms and treatment, along with advice about appropriate health care settings should be provided as part of antenatal or postnatal care.